Review of DOD's Approach to Deriving an Occupational Exposure Level for Trichloroethylene - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Trichloroethylene (TCE) is a solvent that is used as a degreasing agent, a chemical intermediate in refrigerant manufacture, and a component of spot removers and adhesives. It is produced in mass quantities but creates dangerous vapors and is an environmental contaminant at many industrial and government facilities, including facilities run by the U.S. Department of Defense (DoD). It is important to determine the safe occupational exposure level (OEL) for the solvent in order to protect the health of workers who are exposed to its vapors. However, there are concerns that the current occupational standards insufficiently protect workers from these health threats. Review of DOD's Approach to Deriving an Occupational Exposure Level for Trichloroethylene makes recommendations to improve the DoD's approach to developing an OEL for TCE, strengthen transparency of the process, and improve confidence in the final OEL value. This report reviews the DoD's approach using a literature review, evidence synthesis based on weight of evidence [WOE], point-of-departure derivation, physiologically based pharmacokinetic modeling, extrapolation tools, and explores other elements of the process of deriving an OEL for TCE. It examines scientific approaches to developing exposure values and cancer risk levels, defining the scope of the problem, and improving hazard identification.
Keywords: Environment and Environmental Studies

The Promise of Single-Cell and Single-Molecule Analysis Tools to Advance Environmental Health Research: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Over the past decade, single-molecule and single-cell technologies have rapidly advanced healthcare research by enabling scientists to isolate individual cells. On March 7–8, 2019, the National Academies of Sciences, Engineering, and Medicine held a 2-day workshop to explore new single-cell and single-molecule analysis technologies. The participants discussed different uses of new cell technologies, valuable tools and lessons for data analysis, the challenges of translating single-cell genomics to the clinic, and applications in environmental health. This publication briefly summarizes the presentations and discussions from the workshop.
Keywords: Environment and Environmental Studies

Astrochemistry: Discoveries to Inform the Chemical Sciences and Engineering Communities: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Throughout much of human history, space was thought to be a void in which only ions or radicals existed. It was only in the last half of the 20th century that scientists began to discover the existence of molecules, such as ammonia, in space. Discovery has accelerated in the last decade with the installation of new facilities and cutting-edge advances in spectroscopic analysis. These exciting discoveries in astrochemistry—a multidisciplinary field that focuses on the chemical composition of and processes in astrophysical and planetary environments—have potential applications to the general chemistry and chemical-engineering communities. Accordingly, the National Academies of Sciences, Engineering, and Medicine held a workshop on November 8–9, 2018, to (1) explore the chemistry of space—its novel chemicals and reaction mechanisms, (2) discuss information from remote sensing through spectroscopy, and (3) consider discoveries from spacecraft missions in the solar system and laboratory studies of extraterrestrial samples. The ultimate goals of the workshop were to bring the various communities together to explore how discoveries in astrochemistry might provide insights or opportunities for the general chemistry and chemical-engineering communities and to promote understanding in the chemistry and chemical-engineering communities of how they might be able to help the astrochemistry community approach its challenges. This publication summarizes the presentations and discussions that took place during the workshop.
Keywords: Math, Chemistry, and Physics; Engineering and Technology

A Research Agenda for Transforming Separation Science - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Separation science plays a critical role in maintaining our standard of living and quality of life. Many industrial processes and general necessities such as chemicals, medicines, clean water, safe food, and energy sources rely on chemical separations. However, the process of chemical separations is often overlooked during product development and this has led to inefficiency, unnecessary waste, and lack of consensus among chemists and engineers. A reevaluation of system design, establishment of standards, and an increased focus on the advancement of separation science are imperative in supporting increased efficiency, continued U.S. manufacturing competitiveness, and public welfare. A Research Agenda for Transforming Separation Science explores developments in the industry since the 1987 National Academies report, Separation and Purification: Critical Needs and Opportunities. Many needs stated in the original report remain today, in addition to a variety of new challenges due to improved detection limits, advances in medicine, and a recent emphasis on sustainability and environmental stewardship. This report examines emerging chemical separation technologies, relevant developments in intersecting disciplines, and gaps in existing research, and provides recommendations for the application of improved separation science technologies and processes. This research serves as a foundation for transforming separation science, which could reduce global energy use, improve human and environmental health, and advance more efficient practices in various industries.
Keywords: Math, Chemistry, and Physics

Continuous Manufacturing for the Modernization of Pharmaceutical Production: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On July 30-31, 2018, the National Academies of Sciences, Engineering, and Medicine held a workshop titled Continuous Manufacturing for the Modernization of Pharmaceutical Production. This workshop discussed the business and regulatory concerns associated with adopting continuous manufacturing techniques to produce biologics such as enzymes, monoclonal antibodies, and vaccines. The participants also discussed specific challenges for integration across the manufacturing system, including upstream and downstream processes, analytical techniques, and drug product development. The workshop addressed these challenges broadly across the biologics domain but focused particularly on drug categories of greatest FDA and industrial interest such as monoclonal antibodies and vaccines. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Gaseous Carbon Waste Streams Utilization: Status and Research Needs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In the quest to mitigate the buildup of greenhouse gases in Earth's atmosphere, researchers and policymakers have increasingly turned their attention to techniques for capturing greenhouse gases such as carbon dioxide and methane, either from the locations where they are emitted or directly from the atmosphere. Once captured, these gases can be stored or put to use. While both carbon storage and carbon utilization have costs, utilization offers the opportunity to recover some of the cost and even generate economic value. While current carbon utilization projects operate at a relatively small scale, some estimates suggest the market for waste carbon-derived products could grow to hundreds of billions of dollars within a few decades, utilizing several thousand teragrams of waste carbon gases per year. Gaseous Carbon Waste Streams Utilization: Status and Research Needs assesses research and development needs relevant to understanding and improving the commercial viability of waste carbon utilization technologies and defines a research agenda to address key challenges. The report is intended to help inform decision making surrounding the development and deployment of waste carbon utilization technologies under a variety of circumstances, whether motivated by a goal to improve processes for making carbon-based products, to generate revenue, or to achieve environmental goals.
Keywords: Environment and Environmental Studies

Negative Emissions Technologies and Reliable Sequestration: A Research Agenda - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
To achieve goals for climate and economic growth, "negative emissions technologies" (NETs) that remove and sequester carbon dioxide from the air will need to play a significant role in mitigating climate change. Unlike carbon capture and storage technologies that remove carbon dioxide emissions directly from large point sources such as coal power plants, NETs remove carbon dioxide directly from the atmosphere or enhance natural carbon sinks. Storing the carbon dioxide from NETs has the same impact on the atmosphere and climate as simultaneously preventing an equal amount of carbon dioxide from being emitted. Recent analyses found that deploying NETs may be less expensive and less disruptive than reducing some emissions, such as a substantial portion of agricultural and land-use emissions and some transportation emissions. In 2015, the National Academies published Climate Intervention: Carbon Dioxide Removal and Reliable Sequestration, which described and initially assessed NETs and sequestration technologies. This report acknowledged the relative paucity of research on NETs and recommended development of a research agenda that covers all aspects of NETs from fundamental science to full-scale deployment. To address this need, Negative Emissions Technologies and Reliable Sequestration: A Research Agenda assesses the benefits, risks, and "sustainable scale potential" for NETs and sequestration. This report also defines the essential components of a research and development program, including its estimated costs and potential impact.
Keywords: Earth Sciences; Environment and Environmental Studies

Leveraging Artificial Intelligence and Machine Learning to Advance Environmental Health Research and Decisions: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Artificial intelligence (AI) is a technological invention that promises to transform everyday life and the world. Investment and enthusiasm for AI—or the ability of machines to carry out “smart” tasks—are driven largely by advancements in the subfield of machine learning. Machine learning algorithms can analyze large volumes of complex data to find patterns and make predictions, often exceeding the accuracy and efficiency of people who are attempting the same task. Powered by a tremendous growth in data collection and availability as well as computing power and accessibility, AI and machine learning applications are becoming commonplace in many aspects of modern society, as well as in a growing number of scientific disciplines. On June 6–7, 2019, the National Academies of Sciences, Engineering, and Medicine held a 2-day workshop to explore emerging applications and implications of AI and machine learning in environmental health research and decisions. Speakers highlighted the use of AI and machine learning to characterize sources of pollution, predict chemical toxicity, and estimate human exposures to contaminants, among other applications. Though promising, questions remain about the use of AI and machine learning in environmental health research and public policy decisions. This publication summarizes the presentations and discussions from the workshop.
Keywords: Environment and Environmental Studies

Groundwater Recharge and Flow: Approaches and Challenges for Monitoring and Modeling Using Remotely Sensed Data: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Water of appropriate quantity and quality is essential for drinking, sanitation, and food, energy, and industrial production for any society and is derived for most needs from surface- or groundwater sources. Studies suggest that groundwater use in irrigation globally is increasing in total volume as well as a percentage of all water used for irrigation, with the demand for groundwater resources increasing as available primary surface water supplies are depleted. Particularly in arid regions, groundwater may be the most accessible water supply for any purpose, leaving groundwater withdrawals concentrated in areas that are already experiencing water stress. Even in the presence of direct ground observations and measurements of the water table, quantitative evaluation of groundwater storage, flow, or recharge at different scales requires remotely sensed data and observations applied to groundwater models. Resolving the interaction of groundwater storage, flow, and recharge at a scale at which basins are managed requires remotely sensed data and proxy data. In June 2019, the Water Science and Technology Board of the National Academies of Sciences, Engineering, and Medicine convened a workshop to identify scientific and technological research frontiers in monitoring and modeling groundwater recharge and flow in various regions of the world. The goals of the workshop were to assess regional freshwater budgets under major use scenarios, including agriculture, industry, and municipal; examine state of the art research frontiers in characterizing groundwater aquifers, including residence time, quantity, flow, depletion, and recharge, using remotely sensed observations and proxy data; discuss groundwater model uncertainties and methods for mitigating them using sparse ground observations or data and other approaches; and consider our ability to detect which water management strategies that affect groundwater flow and recharge are being used and any changes in their use over time. This publication summarizes workshop presentations and plenary discussions.
Keywords: Earth Sciences

A Research Review of Interventions to Increase the Persistence and Resilience of Coral Reefs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Coral reef declines have been recorded for all major tropical ocean basins since the 1980s, averaging approximately 30-50% reductions in reef cover globally. These losses are a result of numerous problems, including habitat destruction, pollution, overfishing, disease, and climate change. Greenhouse gas emissions and the associated increases in ocean temperature and carbon dioxide (CO2) concentrations have been implicated in increased reports of coral bleaching, disease outbreaks, and ocean acidification (OA). For the hundreds of millions of people who depend on reefs for food or livelihoods, the thousands of communities that depend on reefs for wave protection, the people whose cultural practices are tied to reef resources, and the many economies that depend on reefs for fisheries or tourism, the health and maintenance of this major global ecosystem is crucial. A growing body of research on coral physiology, ecology, molecular biology, and responses to stress has revealed potential tools to increase coral resilience. Some of this knowledge is poised to provide practical interventions in the short-term, whereas other discoveries are poised to facilitate research that may later open the doors to additional interventions. A Research Review of Interventions to Increase the Persistence and Resilience of Coral Reefs reviews the state of science on genetic, ecological, and environmental interventions meant to enhance the persistence and resilience of coral reefs. The complex nature of corals and their associated microbiome lends itself to a wide range of possible approaches. This first report provides a summary of currently available information on the range of interventions present in the scientific literature and provides a basis for the forthcoming final report.
Keywords: Earth Sciences

Long-Term Health Monitoring of Populations Following a Nuclear or Radiological Incident in the United States: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Accidents and terrorist attacks that lead to the release of radioactive materials can cause deaths, injuries, and a range of psychosocial effects in the surrounding community and team of emergency responders. In the United States, federal, state, and local agencies respond with the necessary resources to address the consequences of nuclear and radiological incidents and monitor the affected population. Following the 2011 Fukushima Daiichi Nuclear Power Plant accident and the 2017 Gotham Shield National Level Exercise, the CDC recognized an opportunity to improve their practices by establishing a more efficient and timely health effect surveillance system before another incident occurs. On March 12-13th, 2019, the National Academies convened a workshop to discuss the process for preparing a radiation registry for monitoring long-term health effects of populations affected by a nuclear or radiological incident. Participants assessed existing information, useful practices, and tools for planning a radiation registry that will enhance incident monitoring and response methods. This publication summarizes the discussions and presentations from the workshop.
Keywords: Health and Medicine; Environment and Environmental Studies

Improving the EPA Multi-Sector General Permit for Industrial Stormwater Discharges - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Industrial stormwater is derived from precipitation and/or runoff that comes in contact with industrial manufacturing, processing, storage, or material overburden and then runs offsite and enters drainage systems or receiving waters. In 1987, Congress significantly expanded the National Pollutant Discharge Elimination System (NPDES) program through amendments to the Clean Water Act to include industrial stormwater runoff conveyed through outfalls directly to receiving waters or indirectly through municipal separate storm sewer systems. The added regulation of stormwater in the NPDES program has been challenging. Stormwater is produced throughout a developed landscape, and its production and delivery are episodic. In 2009, the National Research Council released a comprehensive report on the Environmental Protection Agency's Stormwater Program that covered all sectors of the program. This study builds on that report, with a focus on industrial stormwater monitoring and management.
Keywords: Environment and Environmental Studies

A Decision Framework for Interventions to Increase the Persistence and Resilience of Coral Reefs - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Coral reefs are critical to ocean and human life because they provide food, living area, storm protection, tourism income, and more. However, human-induced stressors, such as overfishing, sediment, pollution, and habitat destruction have threatened ocean ecosystems globally for decades. In the face of climate change, these ecosystems now face an array of unfamiliar challenges due to destructive rises in ocean temperature, acidity and sea level. These factors lead to an increased frequency of bleaching events, hindered growth, and a decreasing rate of calcification. Research on interventions to combat these relatively new stressors and a reevaluation of longstanding interventions is necessary to understand and protect coral reefs in this changing climate. Previous research on these methods prompts further questions regarding the decision making process for site-specific interventions. A Decision Framework for Interventions to Increase the Persistence and Resilience of Coral Reefs builds upon a previous report that reviews the state of research on methods that have been used, tested, or proposed to increase the resilience of coral reefs. This new report aims to help coral managers evaluate the specific needs of their site and navigate the 23 different interventions described in the previous report. A case study of the Caribbean, a region with low coral population plagued by disease, serves as an example for coral intervention decision making. This report provides complex coral management decision making tools, identifies gaps in coral biology and conservation research, and provides examples to help individuals and communities tailor a decision strategy to a local area.
Keywords: Earth Sciences

Assuring Data Quality at U.S. Geological Survey Laboratories - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The U.S. Geological Survey (USGS) mission is to provide reliable and impartial scientific information to understand Earth, minimize loss of life and property from natural disasters, and manage water, biological, energy, and mineral resources. Data collection, analysis, interpretation, and dissemination are central to everything the USGS does. Among other activities, the USGS operates some 250 laboratories across the country to analyze physical and biological samples, including water, sediment, rock, plants, invertebrates, fish, and wildlife. The data generated in the laboratories help answer pressing scientific and societal questions or support regulation, resource management, or commercial applications. At the request of the USGS, this study reviews a representative sample of USGS laboratories to examine quality management systems and other approaches for assuring the quality of laboratory results and recommends best practices and procedures for USGS laboratories.
Keywords: Earth Sciences

Care, Use, and Welfare of Marmosets as Animal Models for Gene Editing-Based Biomedical Research: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The marmoset, a type of small monkey native to South America, is a research model of increasing importance for biomedical research in the United States and globally. Marmosets offer a range of advantages as animal models in neuroscience, aging, infectious diseases, and other fields of study. They may be particularly useful for the development of new disease models using genetic engineering and assisted reproductive technologies. However, concerns have been voiced with respect to the development of new marmoset-based models of disease, ethical considerations for their use, the supply of marmosets available for research, and gaps in guidance for their care and management. To explore and address these concerns, the Roundtable on Science and Welfare in Laboratory Animal Use hosted a public workshop on October 22-23, 2018, in Washington, DC. The workshop focused on the availability of marmosets in the United States and abroad; animal welfare and ethical considerations stemming from the use of wildtype and genetically modified marmosets; and standards of housing and care, dietary needs, and feeding requirements for marmosets in captivity. This publication summarizes the presentations and discussions from the workshop.
Keywords: Biology and Life Sciences

Evaluating the Taxonomic Status of the Mexican Gray Wolf and the Red Wolf - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Scientists strive to develop clear rules for naming and grouping living organisms. But taxonomy, the scientific study of biological classification and evolution, is often highly debated. Members of a species, the fundamental unit of taxonomy and evolution, share a common evolutionary history and a common evolutionary path to the future. Yet, it can be difficult to determine whether the evolutionary history or future of a population is sufficiently distinct to designate it as a unique species. A species is not a fixed entity – the relationship among the members of the same species is only a snapshot of a moment in time. Different populations of the same species can be in different stages in the process of species formation or dissolution. In some cases hybridization and introgression can create enormous challenges in interpreting data on genetic distinctions between groups. Hybridization is far more common in the evolutionary history of many species than previously recognized. As a result, the precise taxonomic status of an organism may be highly debated. This is the current case with the Mexican gray wolf (Canis lupus baileyi) and the red wolf (Canis rufus), and this report assesses the taxonomic status for each.
Keywords: Biology and Life Sciences

A Class Approach to Hazard Assessment of Organohalogen Flame Retardants - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In the 1970s, flame retardants began to be added to synthetic materials to meet strict flammability standards. Over the years, diverse flame retardants have been manufactured and used in various products. Some flame retardants have migrated out of the products, and this has led to widespread human exposure and environmental contamination. There also is mounting evidence that many flame retardants are associated with adverse human health effects. As a result, some flame retardants have been banned, restricted, or voluntarily phased out of production and use. This publication develops a scientifically based scoping plan to assess additive, nonpolymeric organohalogen flame retardants as a class for potential chronic health hazards under the Federal Hazardous Substances Act, including cancer, birth defects, and gene mutations.
Keywords: Environment and Environmental Studies

Fostering Transformative Research in the Geographical Sciences - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The central purpose of all research is to create new knowledge. In the geographical sciences this is driven by a desire to create new knowledge about the relations between space, place, and the anthropogenic and non-anthropogenic features and processes of the Earth. But some research goes beyond these modest aims and creates new opportunities for further research, or affects the process of knowledge acquisition more broadly, or changes the way other researchers in a domain think about the world and go about their business. Due to its positive impacts, transformative research can be regarded as inherently having greater value than more conventional research, and funding agencies clearly regard transformative research as something to be encouraged and funded through special programs. Assessments of transformative research funding initiatives are few and provide a mixed picture of their effectiveness. The challenge is whether transformative research can be identified at the time it is proposed rather than after it has been conducted, communicated, and its influence on the discipline has become clear. Fostering Transformative Research in the Geographical Sciences reviews how transformative research has emerged in the past, what its early markers were, and makes recommendations for how it can be nurtured in the future.
Keywords: Earth Sciences

Management Models for Future Seismological and Geodetic Facilities and Capabilities: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Modern geoscience research informs many important decisions and projects, such as geological disaster preparation, natural resource extraction, and global development. This critical research relies on technology and collaboration at state-of-the-art seismological and geodetic facilities. Currently, these facilities provide a wide variety of observation systems that support scientists' understanding of Earth and its changing environmental systems. As emerging technologies develop rapidly, seismological and geodetic facilities have new capabilities and more complex management and research communication systems. This requires a reevaluation of management structures and best practices within these facilities. The National Academies convened a 1.5-day workshop to discuss management models of theoretical seismological and geodetic facilities of the future. Initial discussions built upon a 2015 Incorporated Research Institutions for Seismology community workshop report, which identified current and future capabilities of these research facilities. Management models from other types of scientific facilities were used as a springboard for further discussions about management and decision-making models that could be applied to seismological and geodetic facilities. Workshop participants also emphasized the importance of distributing capabilities among multiple facilities. Lastly, this workshop explored complex management topics in these facilities including instrumentation, user support services, data management, education and outreach, and workforce development capabilities. This publication summarizes the presentations and discussions from the workshop.
Keywords: Earth Sciences

Review of the Final Draft Analysis of Supplemental Treatment Approaches of Low-Activity Waste at the Hanford Nuclear Reservation: Review #3 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In 1943, as part of the Manhattan Project, the Hanford Nuclear Reservation was established with the mission to produce plutonium for nuclear weapons. During 45 years of operations, the Hanford Site produced about 67 metric tonnes of plutonium—approximately two-thirds of the nation's stockpile. Production processes generated radioactive and other hazardous wastes and resulted in airborne, surface, subsurface, and groundwater contamination. Presently, 177 underground tanks contain collectively about 210 million liters (about 56 million gallons) of waste. The chemically complex and diverse waste is difficult to manage and dispose of safely. Section 3134 of the National Defense Authorization Act for Fiscal Year 2017 calls for a Federally Funded Research and Development Center (FFRDC) to conduct an analysis of approaches for treating the portion of low-activity waste at the Hanford Nuclear Reservation intended for supplemental treatment. The third of four, this report provides an overall assessment of the FFRDC team's final draft report, dated April 5, 2019.
Keywords: Environment and Environmental Studies